The pearls and pitfalls of setting high-quality multiple choice questions for clinical medicine - Mergan Naidoo (South African Family Practice)
Multiple choice question (MCQ) examinations have become extremely popular for testing applied knowledge in the basic and clinical sciences. When setting MCQ examinations, assessors need to understand the measures that improve validity and reliability so that the examination accurately reflects the candidate’s ability. This continuing medical education unit will cover the essentials of blueprinting an exam, constructing high-quality MCQs and post hoc vetting of the exam. It is hoped that academics involved in assessments use the content provided to improve their skills in setting high-quality MCQs.